Synthesis and Chraracterizion of Some Lactate Polymers (Journal of the College of Basic Education, 2022)
In this work two new biopolymers were synthesized.We could design a new polymer via ring opening of lactide with Arganine to obtain ester-amide polymer(A1), and grafted lactate through back bone of poly acrylic cid(A2). The prepared polymers (A1) and (A2) were characterized by FTIR and HNMR spectroscopies , physical properties were determined, intrinsic viscosities were measured.Thes two biodegradable polymers were hydrolysis in different pH values.